Hubungan Sikap, Motivasi, dan Prestasi Bahasa Indonesia Siswa Kelas X SMA Negeri 15 Makassar - Asmawati Asmawati (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research aims to understand the relationship between language attitudes, learning motivation, and Indonesian language achievement of class X students at SMA Negeri 15 Makassar. The population of this study was 290 students majoring in Mathematics and Natural Sciences and the sample was determined to be 75 people. The research instrument in the form of a questionnaire has been tested for validity and reliability. This type of research is ex post facto using a quantitative approach. The data analysis technique used is linear regression analysis. The results of the research stated that if the Indonesian language learning achievement in the complete category was 30 students (40%) and in the incomplete category there were 45 students (60%), language attitudes were in the very good category of 20 (26.667%), the good category was 9 (12 %), the poor category is 40 (53.333%), and the very poor category is 6 (8%) so that there is a positive and significant influence between language attitudes and language learning motivation on the Indonesian language learning achievement of class X SMA Negeri 15 Makassar. This means that the more positive the students' language attitudes and language learning motivation, the higher their Indonesian language learning achievement. The conclusion of this research is that the motivation variable for learning Indonesian is in the low category at 48%. So this research shows that language attitudes and language learning motivation are important factors that can develop students' Indonesian language learning achievements. This research has the prospect of further research using different research methods. Apart from that, this research can also be carried out at different educational levels or other subjects.